Dermoscopic features of thin melanomas: a comparative study of melanoma in situ and invasive melanomas smaller than or equal to 1mm - Vanessa Priscilla Martins da Silva; Juliana Kida Ikino; Mariana Mazzochi Sens; Daniel Holthausen Nunes; Gabriella Di Giunta (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Dermoscopy allows the early detection of melanomas. The preoperative determination of Breslow index by dermoscopy could be useful in planning the surgical approach and in selecting patients for sentinel lymph node biopsy. OBJECTIVES: This study aims at describing the dermoscopic features of thin melanomas and comparing melanomas in situ with invasive melanomas less than or equal to 1 mm thick. METHODS: This was an observational retrospective study in which the dermoscopy photographs of 41 thin melanomas were evaluated. Three observers evaluated together 14 dermoscopic criteria. RESULTS: Among thin melanomas, the most frequent criteria were presence of asymmetry in two axes in 95% of cases (39 cases), 3 or more colors in 80.4% of cases (33 cases), atypical dots or globules in 58.5% of cases (24 cases) and atypical network or streaks in 53.6% of cases (22 cases). The group of invasive melanomas presented with a higher frequency and statistical significance (p <0.05) 3 or more colors (OR: 16.1), milky red areas (OR: 4.8) and blue-white veil (OR: 20.4), and a greater tendency to have streaks or atypical network (OR: 3.66). CONCLUSIONS: Thin melanomas tend to have asymmetry in the two axes, 3 or more colors, atypical dots or globules and atypical network or streaks. Melanomas in situ tend to have up to 2 colors, no blue-white veil and no milky red area. Invasive melanomas tend to have 3 or more colors, a milky red area, blue-white veil, and atypical network or streaks. Further studies are needed to confirm these findings.